The Taxation of Miscellaneous Income Sources under the Federal Income Tax Proclamation of Ethiopia: A Critical Analysis - Yemata, Belete Addis (Bahir Dar University Journal of Law, 2024)
Schedule ‘D’ of the Federal Income Tax Proclamation No. 976/2016 taxes income sources that are not taxable under the other income tax schedules. The objective of this article was to create a better understanding of the taxable units and tax bases of the taxing provisions of this schedule and also to explain the many changes introduced under the current Schedule D. To this end, it mainly depends on the doctrinal legal research methods, by which it critically analyzes the relevant legislation, literature, and model tax rules. The discussion revealed that the current Schedule ‘D’ has undergone significant changes. Non-resident taxation is regulated in detail; they are taxed under exclusive provisions in the context of permanent establishment and as residents for their Ethiopian-source income. New tax bases are also added, such as repatriated profit and undistributed profit. The taxation of residual income is part of this introduction. The proclamation also came up with informative definitional provisions for a management fee, technical fee, interest, dividend, and royalty. These not only ease the characterization of the taxpayers and tax bases but also widen the scope of the respective taxation of these sources. The changes introduced in capital gains taxation are also significant in many ways, including widening the assets subject to capital gains tax and providing relatively detailed provisions for the valuation of capital gains. All these changes will be meaningful if the tax administration on the ground is also reformed to reflect the positive changes introduced under the tax laws.